1994
DOI: 10.1055/s-0038-1648851
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Properties of CY 216 and of Its ACLM and BCLM Components in the Rabbit

Abstract: SummaryThis study compares some in vivo pharmacological properties of CY 216 and of its ACLM and BCLM components having a molecular weight above and below 5.4 kDa respectively. The anti-factor Xa/anti-thrombin ratio of these compounds determined in a rabbit plasma system were 2.5 and 1.2 for CY 216 and ACLM respectively while BCLM was devoid of anti-thrombin effect. After bolus intravenous injection, continuous infusion and subcutaneous administration, the clearances of anti-factor Xa activity generated by ACL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
(35 reference statements)
1
8
0
Order By: Relevance
“…ACLM had chains of MW >5,400 Da (5,500–10,000) and BCLM had chains of MW <5,400 Da (2,100–5,300) [22]. The ACLM fraction was shown to have faster clearance measured by anti-Xa activity than both the parent compound and the BCLM fraction.…”
Section: Introductionmentioning
confidence: 99%
“…ACLM had chains of MW >5,400 Da (5,500–10,000) and BCLM had chains of MW <5,400 Da (2,100–5,300) [22]. The ACLM fraction was shown to have faster clearance measured by anti-Xa activity than both the parent compound and the BCLM fraction.…”
Section: Introductionmentioning
confidence: 99%
“…18 It has been postulated that the mechanisms of heparin catabolism consist of a balance between a saturable elimination via the reticuloendothelial system and the non-saturable renal tubular excretion. [18][19][20] Various clearance studies in animal models and clinical settings have shown that the higher LMWHs such as tinzaparin (6,500 Da) and dalteparin (5,700 Da) have a faster, dose dependent clearance, suggesting greater involvement of the endothelial clearance pathway with increasing molecular weights and less renal clearance dependency. 21,22 Rabbat and his group reported all patients who experienced bleeding on dalteparin thromboprophylaxis had trough anti-X a levels below the detection threshold.…”
Section: Discussionmentioning
confidence: 99%
“…The ®fth experimental group (group VII) was given nadroparin 5 anti-Xa, U/ kg/day (Fraxiparine Ò , Sano®-Dogu, Istanbul, Turkey). 19,21,22 All pharmacological agents were given in a volume of 0.2 mL. In all groups, pharmacological agents, including normal saline, were given for 7 days postoperatively.…”
Section: Methodsmentioning
confidence: 99%